Exome Sequencing Identifies a Novel Frameshift Mutation of MYO6 as the Cause of Autosomal Dominant Nonsyndromic Hearing Loss in a Chinese Family. (17th September 2014) - Cheng, Jing; Zhou, Xueya; Lu, Yu; Chen, Jing; Han, Bing; Zhu, Yuhua; Liu, Liyang; Choy, Kwong‐Wai; Han, Dongyi; Sham, Pak C.; Zhang, Michael Q.; Zhang, Xuegong; et al.
Summary Autosomal dominant types of nonsyndromic hearing loss (ADNSHL) are typically postlingual in onset and progressive. High genetic heterogeneity, late onset age, and possible confounding due to nongenetic factors hinder the timely molecular diagnoses for most patients. In this study, exome sequencing was applied to investigate a large Chinese family segregating ADNSHL in which we initially failed to find strong evidence of linkage to any locus by whole‐genome linkage analysis. Two affected family members were selected for sequencing. We identified two novel mutations disrupting known ADNSHL genes and shared by the sequenced samples: c.328C>A in COCH (DFNA9) resulting in a p.Q110K substitution and a deletion c. 2814_2815delAA in MYO6 (DFNA22) causing a frameshift alteration p.R939Tfs*2. The pathogenicity of novel coding variants in ADNSHL genes was carefully evaluated by analysis of co‐segregation with phenotype in the pedigree and in light of established genotype–phenotype correlations. The frameshift deletion in MYO6 was confirmed as the causative variant for this pedigree, whereas the missense mutation in COCH had no clinical significance. The results allowed us to retrospectively identify the phenocopy in one patient that contributed to the negative finding in the linkage scan. Our clinical data also supported the emerging genotype–phenotype correlation for DFNA22.